Aerobic intermittent hypoxic training is not beneficial for maximal oxygen uptake and performance: a systematic review and meta-analysis - Dorelli, G.; Giuriato, G.; Zamboni, G.; Daini, M.; Cominacini, M.; Dalle Carbonare, L. G.; Wang, E.; Crisafulli, E.; Schena, F.; Venturelli, M. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Although many studies have investigated whether aerobic training in hypoxia (IHT) could bring advantages to maximal oxygen uptake (VO2max) and sea-level performance when compared to analogous normoxic training (NT), the literature results are inconsistent. This variability may come from differences in population, training protocols, hypoxic methods, and potential bias. Therefore, a comprehensive meta-analysis with strict inclusion criteria is needed to assess the effects of aerobic IHT on VO2max and performance. This study aims to review previous meta-analyses and analyze all parallel-design studies examining the effect of aerobic IHT compared to NT on VO2max and sea-level aerobic performance. Systematic research was conducted following PRISMA guidelines regarding the effects of aerobic IHT on sea-level VO2max and performance outcomes. The analysis accounted for characteristics of the population, training protocol, hypoxic environment, and publication details. A total of 35 studies involving 524 participants were included. The analysis showed that IHT, compared to NT, did not significantly improve VO2max (p = 0.333), peak power output (p = 0.159), and time to exhaustion (p = 0.410). Subgroup analyses identified no significant differences based on fitness level (p = 0.690) and exercise modality (p = 0.900); however, a publication bias was found (p = 0.004). These results suggest that, despite some enthusiastic findings in the literature, possibly influenced by publication-related biases, aerobic IHT does not offer superior improvement in VO2max and performance compared with NT. Therefore, adding hypoxia to aerobic exercise does not enhance training adaptations.